2020
DOI: 10.1097/sla.0000000000003793
|View full text |Cite
|
Sign up to set email alerts
|

A Single Preoperative Dose of Tranexamic Acid Reduces Perioperative Blood Loss

Abstract: Objective: To review the efficacy and safety of a single dose of intravenous tranexamic acid (TXA) given preoperatively. Summary Background Data: TXA is a synthetic antifibrinolytic that has been used in various surgical disciplines to reduce blood loss, blood transfusions, ecchymosis, and hematoma formation. However, there is no universal standard on the most effective dose and route of TXA administration, limiting its routine use in many centers. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 32 publications
1
66
0
Order By: Relevance
“…The dosage of TXA for local fibrinolysis treatment is 0.5 to 1 g (equivalent to 15 mg/kg) by intravenous injection every 6 to 8 h while the dosage for general fibrinolysis treatment is a single dose of 1 g or 10 mg/kg by intravenous injection [ 38 ]. The meta-analysis by Heyns et al suggested that the most frequently used single dose for a reduction of perioperative estimated blood loss in several types of operation was 15 mg/kg [ 39 ]. A study by Abbasi et al compared two doses of TXA, i.e., 5 and 15 mg/kg during sinus endoscopy surgery [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dosage of TXA for local fibrinolysis treatment is 0.5 to 1 g (equivalent to 15 mg/kg) by intravenous injection every 6 to 8 h while the dosage for general fibrinolysis treatment is a single dose of 1 g or 10 mg/kg by intravenous injection [ 38 ]. The meta-analysis by Heyns et al suggested that the most frequently used single dose for a reduction of perioperative estimated blood loss in several types of operation was 15 mg/kg [ 39 ]. A study by Abbasi et al compared two doses of TXA, i.e., 5 and 15 mg/kg during sinus endoscopy surgery [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tranexamic acid (TXA) is an antifibrinolytic that inhibits fibrin’s plasmin-mediated degradation and is used to stabilize clots and reduce active bleeding. In orthopaedic surgery, tranexamic acid is most notably involved in the elective orthopaedic procedures necessitating transfusion [ 1 , 2 ]. The use of tranexamic acid has become widely accepted in total knee and hip arthroplasty to prevent extensive blood loss and lower transfusion rates, but it can be also beneficial for patients who undergo total shoulder arthroplasty [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…No signi cant difference was found in terms of DVT incidence (P 0.05). There was no signi cant publication bias for postoperative blood loss, transfusion rate, and DVT incidence.Conclusion: When it comes to IV TXA in TKA, a single preoperative dose and an additional dose of TXA may be a better and more feasible way for blood control than a single preoperative dose.Recently, a meta-analysis [15] assessed the e cacy and safety of the e cacy and safety of a single dose of IV TXA given preoperatively. and it showed that preoperative IV TXA reduced perioperative blood loss and transfusion requirements in a variety of surgical disciplines without increasing the risk of thromboembolic events.One RCT[7] showed that with the same total dose of TXA, the preoperative dose and an additional dose of TXA (IV TXA twice) were superior to a single preoperative dose of TXA (IV TXA once) in reducing blood loss in TKA.…”
mentioning
confidence: 99%
“…Recently, a meta-analysis [15] assessed the e cacy and safety of the e cacy and safety of a single dose of IV TXA given preoperatively. and it showed that preoperative IV TXA reduced perioperative blood loss and transfusion requirements in a variety of surgical disciplines without increasing the risk of thromboembolic events.…”
mentioning
confidence: 99%